2020
DOI: 10.1080/09644016.2020.1787063
|View full text |Cite
|
Sign up to set email alerts
|

Do cross-cutting discussions enhance pro-environmental attitudes? Testing green deliberative theory in practice

Abstract: A central notion among green political theorists is that deliberative engagement enhances environmental values. Despite the centrality of this claim within green political theory, there is a lack of empirical research evaluating its promise outside formal deliberative forums. Here, an empirical large-N study is provided that tests whether everyday political discussion between individuals of different political orientations is positively associated with stronger pro-environmental attitudes in the US. The main f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Our study also contributes to the literature on modern climate change skepticism (Brüggemann et al, 2020;Edwards, 2013;Elgesem et al, 2015;Kaiser & Puschmann, 2017;Lewandowsky et al, 2019;Lewandowsky, Oberauer, & Gignac, 2013;van Eck et al, 2020;Walter et al, 2018-02;Williams et al, 2015) and mechanisms of online polarization (Bail et al, 2018;Nordbrandt, 2020;Sunstein, 2002Sunstein, , 2018. Most previous studies focus on the detection and description of polarized networks.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our study also contributes to the literature on modern climate change skepticism (Brüggemann et al, 2020;Edwards, 2013;Elgesem et al, 2015;Kaiser & Puschmann, 2017;Lewandowsky et al, 2019;Lewandowsky, Oberauer, & Gignac, 2013;van Eck et al, 2020;Walter et al, 2018-02;Williams et al, 2015) and mechanisms of online polarization (Bail et al, 2018;Nordbrandt, 2020;Sunstein, 2002Sunstein, , 2018. Most previous studies focus on the detection and description of polarized networks.…”
Section: Discussionmentioning
confidence: 56%
“…While many researchers in the field of such climate change 'echo chambers' (Sunstein, 2002) identify patterns of polarization but refrain from giving clear recommendations on how to prevent or mitigate them (Brüggemann, Elgesem, Bienzeisler, Gertz, & Walter, 2020;Elgesem, Steskal, & Diakopoulos, 2015;Kaiser & Puschmann, 2017), current work has started to propose interventions that promote engagement with cross cutting views and opinions as a way of undermining this type of ideological enclave (Edwards, 2013;Nordbrandt, 2020;van Eck, Mulder, & van der Linden, 2020;Walter, Brüggemann, & Engesser, 2018-02;Williams et al, 2015). However, more recent research in other contexts has suggested that such exposure may backfire (Bail et al, 2018;Paluck, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, a particular branch of democratic theory, investigating and discussing the role of deliberative democracy, has recently argued that based on a range of studies from the domain of environmental policy and attitudes, democratic "deliberation"-inclusive processes of argumentation and not only inclusion and participation as such-matters for public support and trust in political institutions and procedures (116,117). An important finding is how citizens who take part in cross-cutting discussions acquire stronger pro-environmental attitudes and are more trusting toward environmental public policy and green advocacy, irrespective of factors such as party affiliation and sociodemographic background (118). Another lesson is how deliberative approaches must be implemented across institutions and on a "system level"-"democratizing science," disregarding the deliberative features of the institutional environment, will not do (119)(120)(121).…”
Section: Trust In Environmental Governance and Democracymentioning
confidence: 99%
“…She asks: “What if we were to begin with the assumption that people can and do make sensible decisions if they have the evidence and the influence that they need?” and she argues that by designing “a meaningful dialogue between citizens, experts, and governments” the result would be “better outcomes” (Willis, 2021). Empirical research has certainly indicated that deliberation (in both formal and informal settings) can transform public responses to climate change and increase support for environmental policies (Niemeyer, 2013; Nordbrandt, 2021).…”
Section: The Rational Democratic Imaginarymentioning
confidence: 99%